PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PABRIK KELAPA SAWIT (PKS) DARMEX AGRO - Panjaitan, Jonatan Taripar Panjaitan B1021131067 (Jurnal Manajemen Update, 2018)
Every organization and company must be demanded to be able to optimize the human resources owned and how human resources are managed efficiently to obtain maximum results. Likewise with the Palm Oil Mill (PKS) Darmex Agro which is located in the Godang Damar Village, Bengkayang Regency, West Kalimantan. Companies experience problems with the performance of employees who have not been able to achieve the target. This is because the work environment that is not good in the relationship between superiors and subordinates and the lack of motivation or motivation of employees can be seen from the physical needs of employees. Based on this problem researchers conducted research on the influence of the work environment and motivation on employee performance at the Palm Oil Mill (PKS) Darmex Agro. This study uses primary data collected by distributing to 59 samples, namely the entire study population. Data analysis of this study uses multiple linear regression by testing instruments, testing classical assumptions and testing hypotheses with the data processing process using SPSS Version 23. With the work environment and motivation as independent variables and employee performance as the dependent variable. The results of data analysis carried out, the work environment does not have a positive and insignificant effect on employee performance, while motivation has a positive and significant effect on employee performance. Based on the results of the test of determination, work environment and motivation has an effect of 18% on employee performance while 82% is influenced by other variables not examined in this study.Â Keywords: Work Environment, Motivation, and Employee PerformanceDAFTAR PUSTAKABachtiar, Doni. (2012). Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan. Management Analysis Journal, 1 (1): 1-6.Bangun, Wilson. (2012).Manajemen Sumber Daya Manusia. Jakarta: Penerbit Erlangga.Dermawan, A. A. N. Bagus., Sudibya, I Gede A., & Utama, I Wayan M. (2012). Pengaruh Motivasi, Lingkungan Kerja, Kompetensi, Dan Kompensasi Terhadap Kepuasan Kerja Dan Kinerja Pegawai Di Lingkungan Kantor Dinas Pekerjaan Umum Provinsi Bali. Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 6 (2) : 173-184.Â Dewi, Sari K. & Frianto, Agus. (2013). Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan Melalui Motivasi. Jurnal Ilmiah Manajemen, 1 (4): 1055-1065.Ghozali, I. (2013). Aplikasi Analisis Multivariative dengan Program SPSS (7rd ed.). Semarang: Badan Penerbit Universitas Diponegoro.Hasibuan, Malayu. (2016).Manajemen Dasar, Pengertian, Dan Masalah: Edisi Revisi. Jakarta: Bumi Aksara.Irawan, Soehartono. (2008). Metode Penelitian Sosial. Bandung: Remaja Rosdakarya.Mangkunegara, A.A. Anwar Prabu, (2012). Manajemen Sumber Daya Manusia. Bandung: PT Remaja Rosdakarya.Mangkunegara, A.A. Anwar Prabu, (2013). Manajemen Sumber Daya Manusia Perusahaan. Bandung: PT Remaja Rosdakarya.Mathis, Robert L. Dan John H. Jackson (2006). Manajemen Sumber Daya Manusia. Jakarta: Edisi Pertama Salemba Empat.Prahiawan, Wawan. & Simbolon, Nopiyana. (2014). Pengaruh Motivasi Intrinsik dan Lingkungan Kerja terhadap Kinerja Karyawan PT INTIMAS Lestari Nusantara. Jurnal Ekonomi, 5 (1): 35-41.Rivai, Veithzal. Z. (2006). Manajemen Sumber Daya Manusia Untuk Perusahaan. Jakarta: PT. Raja Grafindo Persada.Rivai, Veithzal. Z., Mansyur, Ramly., Thoby, Mutis., & Willy, Arafah. (2014).Manajemen Sumber Daya Manusia Untuk Perusahaan Dari Teori Ke Praktik. Jakarta: PT. Raja Grafindo Persada.Rumengan, Lidya T. & Mekel, Peggy A. (2015). Analisis Lingkungan Kerja Terhadap Kinerja Pegawai Fakultas Ekonomi Dan Bisnis UNSRAT Manado. Jurnal EMBA, 3 (1): 890-899.Â Â Â Â Â Â Â Â Sedarmayanti, 2011. Membangun Dan Mengembangkan Kepemimpinan Serta Meningkatkan Kinerja Untuk Meraih Keberhasilan. Bandung: PT. Refika Aditama.Septianto. (2010). â€œManajemen Sumber Daya Manusiaâ€. Bandung: Alfabeta.Septianto, Dwi. (2010). Pengaruh Lingkungan Kerja dan Stress Kerja ( Skripsi yang tidak dipublikasikan), Universitas Diponegoro, Indonesia.Siagian, James. (2013). Metode Penelitian Sosial Praktis. STAIN Pontianak Press.Sidanti, Heny. (2015). Pengaruh Lingkungan Kerja, Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Negeri Sipil Di Sekretariat DPRD Kabupaten Madiun. Jurnal JIBEKA, 9 (1): 44-53.Sofyandi, H. (2013). Manajemen Sumber Daya Manusia. Yogyakarta: Graha Ilmu.Sugiyono. (2014). Metode Penelitian Bisnis (Pendekatan Kuantitatif, Kualitatif, dan R&D). Bandung: Alfabeta.Sugiyono. (2014). Statistika Untuk Penelitian. Bandung: Alfabeta.Sutrisno, H.E. (2009). Manajemen Sumber Daya Manusia. Jakarta: Kencana Prenada Media Group.Tjoanda, P. M., Irianto, J., & Suaedi, F. (2014). Pengaruh Motivasi Karyawan Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Srikandi Plastik Di Sidoarjo. Jurnal Pengembangan Sumber Daya Manusia, 1 (23): 1-8.Umar, H. (2010). Desain Penelitian MSDM dan Perilaku Karyawan Paradigma Positivistik danBerbasis Pemecahan Masalah. Jakarta : PT. Raja Grafindo Persada.Winardi, J. (2011). Motivasi dan Pemotivasian dalam Manajemen. Jakarta: Rajawali Pers.Â Â Â Â Â Â